Avoidance Melalui Leverage Sebagai Variabel Moderasi : Kepemilikan Institusional, Komisaris Independen, Beban Pajak Tangguhan (Studi kasus pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2016 - 2020) - Ningsih, Neni Sri Wayuni; Agusty, Dhia Fadhila; Sari, Desi Permata; Ramadhanu, Agung (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
This research aims to discover the effects of institutional ownership, independent commissioners, and deferred tax expense on tax avoidance with leverage as a moderating variable. Institutional ownership, independent commissioners, and deferred tax expense are used as independent variables, and tax avoidance is used as the dependent variable. And leverage is used as a moderating variable. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The method of determining the sample in this study used a purposive sampling method so that, from 196 populations, a sample of 63 companies was obtained. The datasets in this study were analyzed using multiple linear regression techniques.techniques. The results show that institutional ownership and deferred tax expense partially affect tax avoidance. Meanwhile, the independent commissioner has no significant effect on tax avoidance. Institutional ownership moderated by leverage affects tax avoidance, while independent commissioners and deferred tax expense moderated by leverage do not affect tax avoidance.